HUBUNGAN DUKUNGAN KELUARGA DENGAN PRAKTIK PERAWATAN TALI PUSAT DI PUSKESMAS BAAMANG I SAMPIT TAHUN 2019 - Wiwid Cia (Jurnal Ilmiah Kebidanan dan Kesehatan Wanita, 2020)
Background : The number of cases of neonatal tetanus in 2016 was 33 cases. Tetanus neonatorum is caused by Clostridium tetani bacillus. One effort to solve the problem and reduce the infant mortality rate due to infections umbilical cord and neonatal tetanus among others are given tetanus toxoid every pregnancy is very beneficial to prevent neonatal tetanus than it was supposed sterility must be very careful when cutting the umbilical cord and for next umbilical cord practice. The role of the family support is very influential at the time mother became a parent because of he will be responsible for baby care, one of which is to do umbilical cord care. Purpose : Knowing correlation between family support with umbilical cord care practices in Baamang I Public Health Central Sampit. Methods : Research type is Analytic research with a cross sectional design and accidental technique. The sampling used of in this research was a 30 samples. The dependent variable is umbilical cord care practice, and the independent variabel is family support. Collecting data using questionnaires. Location research in Baamang I Public Health Center Sampit. Result : The result of this study revealed that 18 postpartum mothers (60%) received less support from their family and 12 postpartum mothers (40%) received support from their family. 13 postpartum mothers (43.3%) do umbilical cord care correctly and 17 postpartum mothers (56.6%). do not properly care for the umbilical cord. From the results of the chi-square test was obtained a significant relationship between family support with umbilical cord care practices with ? value : 0,035 Conculotion : There are correlation between family support with umbilical cord care practices